Self-reflection as a lens: a qualitative study of Nepalese undergraduate medical students’ perceptions towards virtual community posting during COVID-19 pandemic - Rajbhandari, Ajay Kumar; Pathak, Pratiksha; Thapa Pachya, Ambika; Subedi, Madhusudan; Shrestha, Shrijana (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Self-reflection is a vital pedagogical tool for fostering professional competencies in medical education. The transition to virtual platforms during the COVID-19 pandemic posed unique challenges for experiential learning components like community postings. This study aimed to explore the perceptions and experiences of undergraduate medical students at Patan Academy of Health Sciences (PAHS), regarding their virtual community posting through self-reflections.Method: An exploratory qualitative research method was used. All 56 third-year undergraduate medical students at PAHS who completed a five-week long virtual posting at Primary Health Care Centers were included in this study. Written self-reflection of individual students during and after the completion of virtual posting was collected. Thematic analysis of the reflections was done to explore their perceptions on transitioning from conventional on-site to virtual community-based learning. Ethical approval was obtained from PAHS Institutional Review Committee.Result: Analysis of reflections revealed four primary themes: appreciation, innovation, effectiveness, and constraints of the online learning modality. Participants valued the innovative approach for maintaining academic continuity during the pandemic and noted an expanded range of learning opportunities. However, the most significant limitations identified were the lack of hands-on clinical experience and direct community interaction, which were deemed irreplaceable for experiential learning.Conclusion: Virtual postings offered a valuable, flexible educational model that enhanced theoretical knowledge but could not be a substitute for the on-site clinical experience and community exposure. However, it could be a viable alternative during crises such as pandemics or natural disasters when physical placement is not feasible.